Efficacy of PCR-based open reading frame typing assay for outbreak investigation of metallo-β-lactamase-producing Pseudomonas aeruginosa in hematology unit. Issue 12 (December 2018) - Nakamura, Ayako; Misawa, Shigeki; Chonan, Masayoshi; Kawakami, Takaaki; Horii, Takashi; Komatsu, Norio; Ohsaka, Akimichi
Abstract: We investigated the efficacy of the PCR-based open reading frame typing (POT) assay for outbreak investigation of metallo-β-lactamase (MBL)-producing Pseudomonas aeruginosa (MBL-PA). A total of 53 P . aeruginosa isolates were detected between January 2010 and December 2012 on a hematology ward, of which 6 were identified as MBL-PA with the bla IMP-1 gene. The POT assay revealed the same genotype (207-41) in 3 of 6 MBL-PA, suggesting an outbreak caused by a single strain. Environmental investigation of bathroom samples revealed the same POT genotype (207-41) as those of the clinical isolates and no other MBL-PA strains. Genetic relatedness of the MBL-PA isolates was confirmed by the DiversiLab repetitive-sequence-based PCR typing system, suggesting the POT type 207-41 as a genetically identical clone. The POT assay can be successfully applied to MBL-PA genotyping.